Factors Affecting Budget Absorption at Regional Apparatus Organizations - Subhiningsih, Retno Ambarwati; Asnawi, Said Kelana; Sufyati, Sufyati (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
This study aims to analyze the factors that influence the absorption of expenditure budgets at the Regional Apparatus Organization in South Tangerang City. The research sample is respondents who hold positions in areas related to the budget, including commitment-making officials, technical implementation officials, officials who sign pay warrants and expenditure treasurers at Regional Apparatus Organization in South Tangerang City. The research method used is quantitative method with multiple linear regression analysis tools. The variables in this study are five independent variables and one dependent variable, namely: budget planning (X1), administrative processes (X2), human resources (X3), goods and services procurement documents (X4), budget changes (X5), while one dependent variable is budget absorption (Y). The results showed that simultaneously budget planning, administrative processes, human resources, goods and services procurement documents, budget changes had a significant effect on the absorption of revenue and expenditure budgets at Regional Apparatus Organization s in South Tangerang City. Furthermore, partially budget planning and human resources have a significant effect on the absorption of revenue and expenditure budgets at Regional Apparatus Organization in South Tangerang City. However, partially administration, goods and services procurement documents, budget changes have no significant effect on the absorption of revenue and expenditure budgets at Regional Apparatus Organization in South Tangerang City. In this study the regression equation is as follows Y=5,964+0,246X_1-0,1X_2+0,239X_3-0,62X_4+0,176X_5.